Moderating Role of COVID-19 Crisis on Firm Leverage Speed of Adjustments: Evidence from Pakistan - Hussain, Muhammad Mazhar; Mohammad, Khalil Ullah (Audit and Accounting Review, 2022)
This study evaluates the impact of firm-specific, industry-specific, and macroeconomic determinants on the speed of capital structure adjustment and to see if COVID-19 impacted these relationships. Using quarterly data of all listed non-financial firms in Pakistan for the period 2016-2021, a dynamic panel data model using the generalized method of moment (GMM) was used for estimation. It was found that firm size, growth potential, non-debt tax shield, and GDP growth positively impact firm leverage, while profitability and tangibility negatively impact leverage. The study found evidence of convergence to target leverage by Pakistani firms. These firms' capital structure adjustment speed was estimated as 16.7% per quarter. Moreover, COVID-19 was not found to affect the adjustment speed of firms, directly. Furthermore, greater distance from target leverage, growth potential, and GDP growth rate resulted in a lower speed of adjustment, whereas higher profitability and liquidity were found to increase the speed of adjustment.